Prevalence of infection in patients with temporary catheter for hemodialysis in a teaching hospital - Palmiane de Rezende Ramim Borges; João Bedendo (Universidade Estadual de Maringá, 2017)
This study aimed to determine the prevalence of infection related to the provisional catheter for hemodialysis in a teaching hospital and evaluate the risk factors associated with these infections.  A cross-sectional study analyzed by descriptive statistics and parametric tests. It was found that out of 129 patients, 48.8 % had catheter-related infection in hemodialysis, 65 % were male, 33.3 % were 60 years old and over, and 88 % of patients were admitted to intensive care unit. The prevalence of infection in this group was high, and the vast majority of diagnoses of infection were empirical. Given this, it is suggested to establish the routine culture of the catheter tip in all cases of suspected catheter infection to improve the quality of patient care, and the relentless pursuit of the causes that trigger the infection process in line with good practice from across the healthcare team.